The art of intrusion : the real stories behind the exploits of hackers, intruders & deceivers - Mitnick, Kevin, 1963-2023 (Wiley Pub., 2005)
Hacker extraordinaire Kevin Mitnick delivers the explosive encore to his bestselling The Art of Deception Kevin Mitnick, the world's most celebrated hacker, now devotes his life to helping businesses and governments combat data thieves, cybervandals, and other malicious computer intruders.